Isolation of Talaromyces marneffei from the Skin of an Egyptian Mongoose (Herpestes ichneumon) in Portugal - Matos, A.C. (2019)
We report a case of Talaromyces marneffei skin infection in an Egyptian mongoose ( Herpestes ichneumon) in Portugal. The isolated fungus was identified through its mycologic characteristics, morphology, and PCR amplification.